Recovery and purification of epidermal growth factor from fermentation broth using expanded bed chromatography - Rosti, Ira Amira (2013)
Epidermal growth factor (EGF) is a single chain polypeptide that exhibit generous bioactivities effect on proliferation of cells in cosmetics and pharmaceutical industries. It is well known that biopharmaceutical production cost relies very much on purification steps. Due to therapeutic potential and high market value of EGF,development of an efficient and cost-effective production process is required. Integrative chromatographic technique, Expanded Bed Adsorption (EBA), may be used to solve the separation problems related to the effect of particulates in the recovery process. Simple and rapid quantification method of the target protein needs to be developed for process monitoring and control during recovery and purification processes. Performance of EGF recovery and purification with the presence of two different cell types, Escherichia coli (E. coli) homogenate (treated with osmotic shock) and Pichia pastoris (P. pastoris) intact cells, were demonstrated using EBA. Optimum adsorption and elution experiments were performed in a batch mode. Biomassadsorbent interaction and stability of bed formation were evaluated using Cell Transmission Index (CTI) and zeta potential. In order to monitor the purification performances, surface plasmon resonance (SPR) was used for the quantification of EGF during recovery and purification processes. An analysis method using SPR was developed by assessing the best choice of suitable biomolecular recognition for the quantification of EGF. Two types of EGF antibody, monoclonal (mAb) and polyclonal (pAb), were immobilized on the surface of chip and validated for its characteristics including specificity, range, intermediate precision and repeatability,recovery, dilution paradox and stability. Kinetics and affinity constants of antibodies-EGF binding were also evaluated using 1:1 Langmuir interaction model (global fitting). Polyclonal antibody (pAb) is more suitable to be used as a stable ligand to quantify EGF continuously from the consideration of kinetics, binding rate and shelf life assessment. pAb has a better affinity (KD = 7.39 x 10-9 M) than monoclonal antibody (mAb) (KD = 9.54 x 10-10 M). From the kinetics evaluation, it was found that pAb has a faster reaction rate during sample injection, slower dissociation rate during buffer injection and higher level of saturation state than monoclonal antibody (mAb). Besides, pAb has a longer shelf life and greater cycle can be run. For purification of EGF, maximum binding of target protein can be achieved at pH 4.5 with less biomass adhesion. Recovery of EGF from E. coli homogenate gave higher grade purification as compared to P. pastoris intact cells using the preferred elution agents. A purification factor of 2.5 was achieved after increasing the elution efficiency using lower ionic strength of elute. Since 100% Cell Transmission Index (CTI) was achieved, interaction of biomass-adsorbent could be considered as not an obstacle. Repulsion between negative mixed mode adsorbent with negatively charge surface of biomass at particular condition is expected due to electrostatic charge interaction. Results from this study have demonstrated that EBA and SPR can be used as an attractive alternative for efficient and cost-productive procedure in the purification of EGF from fermentation broth with less biomass adhesion. With this approach, high overall product yield with reduced process time and cost are expected in the large scale industrial process for direct recovery and purification of recombinant protein from fermentation broths.